A single haplotype hyposensitive to light and requiring strong vernalization dominates Arabidopsis thaliana populations in Patagonia, Argentina. Issue 13 (2nd May 2017) - Kasulin, Luciana; Rowan, Beth A.; León, Rolando J.C.; Schuenemann, Verena J.; Weigel, Detlef; Botto, Javier F.
Abstract: The growing collection of sequenced or genotyped Arabidopsis thaliana accessions includes mostly individuals from the native Eurasian and N. African range and introduced North American populations. Here, we describe the genetic and phenotypic diversity, along with habitats and life history, of A. thaliana plants collected at the southernmost end of its worldwide distribution. Seed samples were harvested from plants growing in four sites within a 3500‐km 2 ‐area in Patagonia, Argentina, and represent the first germplasm to be collected in South America for this species. Whole‐genome resequencing revealed that plants from the four sites and a Patagonia herbarium specimen collected in 1967 formed a single haplogroup (Pat), indicating that the phenotypic variation observed in the field reflected plastic responses to the environment.admixture and principal components analyses suggest that the ancestor of the Pat haplogroup either came from Italy or the Balkan/Caucasus regions of Eurasia. In the laboratory, plants from the Pat haplogroup were hyposensitive to continuous red (Rc) and shade light, with corresponding changes in the expression of phytochrome signalling genes. Pat had higher PIF3 and PIF5 and lower HY5 expression under Rc light; and lower expression of PIL1, ATHB2 and HFR1 under shade compared to Col‐0. In addition, Pat plants had a strong vernalization requirement associated with high levels of FLC expression. We conclude that including Pat in studies of natural variation and in comparison with other introduced populations will provide additional information for association studies and allow for a more detailed assessment of the demographic events following colonization.